Granulosa-cell tumor after ovarian stimulation: A case report - Zohreh Yousefi; Hekmat Khalilifar; Amir Hosein Jafarian; Behrouz Davachi; Leila Mousavi Seresh; Nooshin Babapour; Laya Shirinzadeh; Mina Baradaran (Shahid Sadoughi University of Medical Sciences, 2018)
Abstract Background: Ovarian superovulation and increased follicle-stimulating hormone concentration for infertility treatment may be the risk factors of developed granulosa-cell tumor. The aim of this report is to introduce a case of granulosa-cell tumor which was discovered after ovarian stimulation. Case: A 31-yr-old woman with clinical presentation of massive abdominal distention was referred to the gynecology and oncology department of an academic hospital, Mashhad University of Medical Sciences in Aug 2017. She had the history of secondary infertility and was undergoing In Vitro Fertilization protocol and ovarian stimulation, but, the cycle was canceled. The patient suffered from gradual abdominal distention one month after the end of IVF procedure despite pregnancy failure. 2-3 months after management of the ovarian hyperstimulation syndrome, investigation revealed large ovarian mass and increased tumor marker inhibin. Exploratory laparotomy was performed and revealed stage III ovarian cancer. The final pathology report indicated juvenile granulosa cell tumor. So, optimal surgical staging and cytoreductive surgery without fertility preserving were perfumed. Chemotherapy was recommended due to the advanced stage of ovarian cancer. Unfortunately, she experienced metastatic diseases in pelvic and abdomen in less than six months; and currently is receiving the second and third line chemotherapy. Conclusion: Persistent ovarian enlargement or ascites during or after infertility treatment should be carefully considered and managed